The Mind the violent mind - Amsden, Justin; Freeth, Martin; Raven, Keith (The Mind series, 1988)
Changes in anatomy and chemistry of the brain can cause violent bahavior. In this episode, scientists suggest that even the acts of a serial killer may have a biological or genetic basis. While science delves into the natural aggresive instincts within the mind and measures the probability of violent acts, new scientific data raises difficult questions about the punishment of criminals. This is juxtaposed to the legal system's demand for immutable evidence of guilt or innocence.